Gender and crime in the life pathways of young women offenders: contrasting the narratives of girls and professionals - Matos, Raquel (2022)
This chapter focuses on gender and crime in the life pathways of young women offenders through the analysis of the narratives of both young women serving prison sentences and professionals who deal with young offenders. In terms of theoretical framework, it is based on the feminist approaches that criticize, deconstruct and propose to rebuild the way women offenders have long been conceptualized in criminological theories. The two empirical studies hereby presented were developed in Portugal. In the first, 12 young women prisoners (16–22 years old) were interviewed. In the second study, 43 professionals who deal with youth delinquency on a daily basis were asked about their global perspectives on “youth delinquent groups” and their specific arguments about the involvement of girls in such groups. Various understandings of crime emerged from the young women’s narratives about their life pathways, supporting the rejection of the traditional concepts of female juvenile delinquency. Such findings contrast with the gender stereotypes and ambivalence that seem to characterize the professionals’ perspectives on female delinquency. Our findings emphasize the advantages of assuming a gender perspective and of contrasting different narratives on young women’s delinquent behaviour.